PENGGUNAAN PERMAINAN TEKA-TEKI SILANG DALAM PEMBELAJARAN KOSAKATA UNTUK SISWA KELAS 8 DI SMPI DARUDDA’WAH PUNGGUR - Nursa'adah, Nursa'adah; Ismu Purwaningsih, Dewi; Yolanda, Alvina (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2024)
Nursa’adah, 2024. The Use Of Crossword Puzzle Games in Learning Vocabulary for 8th Graders of SMPI Darudda’wah Punggur English Education Study Program Teacher Training and Education Faculty Nahdatul Ulama University West Kalimantan Kubu Raya. This type of research is quantitative research, which involves one class intending to know the effect of crossword puzzle games on students' vocabulary mastery of English in class 8th SMPI Darudda’wah Punggur Kubu Raya Regency. The research design used is the one-group pretest and posttest, research subjects are class 8th SMPI Darudda’wah, totaling 16 students. The data collection teaching outcomes test for measuring learning outcomes of English vocabulary mastery with the application crossword method. The analysis results show that known assessments from the pre-test obtained a mean of 58.13, maximum value of 70, minimum value of 40, and standard deviation of 10.468, and known assessments from the post-test obtained a mean of 66,88, maximum value of 80, minimum value of 50, and standard deviation 7,042. Based on the results of the paired sample t-test, the sig value obtained 0.006 < 0,05, and the value T count 3,217 > 1,745, so it can be concluded that the use of crossword puzzle media significantly improved vocabulary mastery in class 8th SMPI Darudda’wah punggur.